Theory Planned of Behavior Perspective in Entrepreneurship Intense Study - Z. Fitriyah; B. S.A. Utami (Nusantara Science and Technology Proceedings)
The difficulty of getting job results in high levels of unemployment and poverty. This is due to a large number of people who find it difficult to get a decent job. The high rate of unemployment is actually created by educated groups so that it can be said that higher education does not guarantee a person gets a decent job. One effort that can reduce the unemployment rate is by entrepreneurship. Entrepreneurship is important for a country as a supporter of an increase in the economic level, entrepreneurs can create new creative industries that stimulate the interest of other candidates to join and even be able to provide new jobs for others and able to absorb more workers with the aim of reducing unemployment problems. The purpose of this study was to see how much influence subjectivity norms, personal attitude, perceived behavior, and motivation toward student entrepreneurial intentions. This research was conducted at the Faculty of Economics and Business and took a sample of 156 UPN Veteran East Java students. The technique of collecting data through a questionnaire. Processing data obtained using PLS (Partial Least Square). The test results from the study show that there is a positive and significant influence between the variables of subjective norms, personal attitude, perceived behavior and motivation towards the intention of student entrepreneurship. This can be recommended, to the management of the Faculty of Economics and Business in order to convince the mindset of students so that they have an interest in entrepreneurship, instill talent and explore the potential of students to become students. In addition, faculties in the future will be able to expand their study programs that focus on entrepreneurship.